Landscape, places of knowledge, and religion on Iron-age Bornholm (AmS-Skrifter, 2026)
This paper addresses religious knowledge from a landscape perspective and explores different ways knowledge in a past oral society could have been embedded in and circulated through space and materiality. Drawing on Christian Jacob’s concept of lieux de savoir, the article focuses on the island of Bornholm in the Iron Age, investigating various scales of knowledge transmission. It looks at knowledge in relation to central places, sacral place names, and monumental communication lines, as well as to gold bracteates and gold foil figures. Through the examples, the paper reflects on the production and social distribution of knowledge and differences between open and concealed communication, common knowledge shared by all, and esoteric knowledge passed on in narrowly defined circles.